Legal Protection for the Parties in A Agreement : Civil Law Studies - Sanusi Sanusi; Mukhidin Mukhidin; Fajar Ari Sudewo; Ervin Hengki Prasetyo (International Journal of Law, Crime and Justice, 2024)
Civil law is a branch of law that regulates relations between individuals or legal entities in terms of their personal interests. In civil law, a contract is considered a legal agreement between two or more parties who give each other promises to do or not do something. This research uses normative methods with qualitative research methods which use primary legal material sources, such as laws and the Criminal Code as well as secondary materials, such as books and journals. Contract law is an agreement between two or more people which creates an/an obligation to do or not do a specific thing. There are elements that are considered valid and binding. This includes the existence of an agreement from two or more parties, the desire or aim of the parties for legal consequences to arise, the legal consequences of the agreement only bind the parties and do not bind third parties, and certain agreements must be made in accordance with the law. There are legal principles in contract law, including freedom of contract, consensualism, and pacta sunt servanda. The conclusion is that contract law contains elements that are considered valid and principles in making agreements as well as the influence of written evidence in making a contract which provides legal certainty and as proof of the agreement. There are two main doctrine in contract law, classical and contemporary doctrine. The classical doctrin emphasize the legal certainty to be the core of legal issue in contract law. The doctrine noted that every single purpose of parties should be stated in contract in order to put binding eJect to the parties. It also distinguish the concept of breach of contract and tort. The petition for breach of contract should be based on the concept of breach of contract instead tort. In reverse, the contemporary doctrine emphasize the justice and appropriateness aspect in a contract. It recognized the contract as the whole process held by pre-contractual phase, contractual phase, and post- contractual phase. Hence, it realize the existence of impact toward promises stated by one party to others which is distinctly diJerent to the classical doctrine that neglect the impact of pre- contractual. The contemporary doctrine eliminates the distinguishing of breach of contract and tort as the basic of the sue because breach of contract was the specific genus of tort.